Serious games para la puesta en valor de la cultura. Un caso práctico: SUM - Jon Arambarri Basáñez; Leire Armentia Lasuen; Unai Baeza Santamaría (Virtual Archaeology Review)
Although video games and serious games are based on similar technologies, their uses and purposes are completely different. Some examples of what serious games are designed for include achieving objectives, acquiring complex life skills and promoting cooperation at work. The main goal of a serious game is to make culture accessible to everyone using Information and Communication Technologies. This paper will present the case study of Sum, an on-line serious game which aims to promote Spanish culture as a global culture that has been directly influenced by the historical events that have taken place in the past throughout the country.